2018
DOI: 10.1590/2317-1545v40n2190927
|View full text |Cite
|
Sign up to set email alerts
|

Physiological potential of soybean seeds treated in the industry with and without the application of dry powder

Abstract: -In soybean crops, industrial seed treatment is widely adopted, and it has allowed the development of new technologies, such as the use of dry powders. This work aimed to evaluate the effect of the industrial treatment, with and without the additional application of dry powder, on the physiological potential of soybean seeds. The experimental design was completely randomized, in a 4×2 factorial scheme, with four replications. Four chemical treatments were evaluated: 1) control, 2) carbendazim + thiram + thiame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
2
5
0
1
Order By: Relevance
“…In this context, it is important to stress that Abati et al (2018), found different responses in relation to germination, depending on soybean cultivar. These authors considered the use of dry powder resulted in lower speed of germination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is important to stress that Abati et al (2018), found different responses in relation to germination, depending on soybean cultivar. These authors considered the use of dry powder resulted in lower speed of germination.…”
Section: Resultsmentioning
confidence: 99%
“…The use of dry powder in seed treatment usually accelerates the natural drying process of the product but can result in future imbibition damage in seeds (Abati et al, 2018). These difficulties may occur during the imbibition process and is caused by a negative action of the fast water uptake on cell membranes, thus resulting in problems during germination (Toledo et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Especially soil pathogenic fungi and insect pests can have negative impacts in the initial stages of crop development (França-Neto et al, 2016) and on establishing plant stand. Mixtures of determined active ingredients are widely used in chemical treatment, but these mixtures may be phytotoxic to seeds and thus reduce their physiological potential ( Abati et al, 2018;Santos et al, 2018;Abati et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical treatments used to be applied before sowing, both on the farm as well as in at the resale stage, using specific machines. However, with the nationwide development of agriculture, seed companies came to adopt techniques that maximize crop yield, e.g., an industrial process of seed treatment, in which the seeds are treated in the proper processing stage and later bagged and stored until sowing (BRZEZINSKI et al, 2015;ABATI et al, 2018).…”
Section: Introductionmentioning
confidence: 99%